2010
DOI: 10.1038/nn.2619
|View full text |Cite
|
Sign up to set email alerts
|

Dnmt3a regulates emotional behavior and spine plasticity in the nucleus accumbens

Abstract: Despite abundant expression of DNA methyltransferases (Dnmt’s) in brain, the regulation and behavioral role of DNA methylation remain poorly understood. We find that Dnmt3a expression is regulated in mouse nucleus accumbens (NAc) by chronic cocaine and chronic social defeat stress. Moreover, NAc specific manipulations that block DNA methylation potentiate cocaine reward and exert antidepressant-like effects, whereas NAc specific Dnmt3a overexpression attenuates cocaine reward and is pro-depressant. On a cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
461
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 560 publications
(506 citation statements)
references
References 49 publications
29
461
0
7
Order By: Relevance
“…However, these studies have focused on DNA methylation either on particular brain regions, such as the nucleus accumbens (NAc) (Anier et al, 2010;LaPlant et al, 2010), the hippocampal pyramidal neurons (Novikova et al, 2008), the striatum (Carouge et al, 2010) and the prefrontal cortex (PFC) (Tian et al, 2012b), or on specific genes, such as the protein phosphatase-1 catalytic subunit (PP1c) promoter, the fosB promoter (Anier et al, 2010), the cyclin-dependent kinase-like 5 (CDKL5) gene (Carouge et al, 2010) and not the whole genome (global methylation). For instance, it was shown that the PFC exhibits hypo-methylation, while the striatum of the brain exhibits hyper-methylation in response to chronic cocaine exposure in mice and rats (Carouge et al, 2010;Tian et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have focused on DNA methylation either on particular brain regions, such as the nucleus accumbens (NAc) (Anier et al, 2010;LaPlant et al, 2010), the hippocampal pyramidal neurons (Novikova et al, 2008), the striatum (Carouge et al, 2010) and the prefrontal cortex (PFC) (Tian et al, 2012b), or on specific genes, such as the protein phosphatase-1 catalytic subunit (PP1c) promoter, the fosB promoter (Anier et al, 2010), the cyclin-dependent kinase-like 5 (CDKL5) gene (Carouge et al, 2010) and not the whole genome (global methylation). For instance, it was shown that the PFC exhibits hypo-methylation, while the striatum of the brain exhibits hyper-methylation in response to chronic cocaine exposure in mice and rats (Carouge et al, 2010;Tian et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…La méthylation d'un gène est généralement suivie par sa répression, consécu-tive au recrutement d'un complexe répresseur qui peut, soit empêcher la liaison de la machinerie transcriptionnelle à l'ADN, soit entraîner la chromatine vers un état fermé. Notons que l'administration répétée de cocaïne régule l'expression de la DNMT3A dans le striatum de rongeurs [15][16][17]. À l'opposé, la réduction de l'activité de la DNMT3A, soit par inhibition pharmacologique, soit par invalidation du gène correspondant, a pour effet d'accroître les réponses comportementales à la cocaïne [15].…”
Section: La Méthylation/déméthylation De L'adnunclassified
“…Notons que l'administration répétée de cocaïne régule l'expression de la DNMT3A dans le striatum de rongeurs [15][16][17]. À l'opposé, la réduction de l'activité de la DNMT3A, soit par inhibition pharmacologique, soit par invalidation du gène correspondant, a pour effet d'accroître les réponses comportementales à la cocaïne [15]. Les recherches concernant les mécanismes de déméthy-lation de l'ADN ont fait l'objet d'âpres débats.…”
Section: La Méthylation/déméthylation De L'adnunclassified
“…Given the above, one cannot exclude that at least some of the epigenetic alterations reported in diseased postmortem brain are not necessarily stable imprints that exist for very long periods of time, and instead, could potentially reflect a mechanism that operated on a much shorter time scale before death, perhaps lasting only a few days or even less. The rapidly growling list of conditions acutely affecting the regulation of chromatin structure and function in brain includes ischemia (Endres et al, 2000), and exposure to environmental toxins (Bollati et al, 2007;Desaulniers et al, 2005;Salnikow and Zhitkovich, 2008), nicotine (Satta et al, 2008), alcohol (Marutha Ravindran and Ticku, 2004), psychostimulants (LaPlant et al, 2010;Numachi et al, 2007;Numachi et al, 2004), antipsychotic drugs (Cheng et al, 2008;Dong et al, 2008;Li et al, 2004;Mill et al, 2008;Shimabukuro et al, 2006) and mood stabilizers such as lithium (Kwon and Houpt, 2010) and valproate (Bredy et al, 2007;Dong et al, 2008).…”
Section: Epigenetic Markings In Brainfstate or Trait?mentioning
confidence: 99%